2018
DOI: 10.1017/s0007114518000107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of inadequate micronutrient intakes of Canadian long-term care residents

Abstract: This study determines the prevalence of inadequate micronutrient intakes consumed by long-term care (LTC) residents. This cross-sectional study was completed in thirty-two LTC homes in four Canadian provinces. Weighed and estimated food and beverage intake were collected over 3 non-consecutive days from 632 randomly selected residents. Nutrient intakes were adjusted for intra-individual variation and compared with the Dietary Reference Intakes. Proportion of participants, stratified by sex and use of modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Our findings support observations by others showing zinc deficiency among older adults living in the community [61] and institutions [47]. A further study of 632 long-term care residents in Canada, who were aged 65 and over, also reported a dietary inadequacy of zinc [62].…”
Section: Zincsupporting
confidence: 91%
“…Our findings support observations by others showing zinc deficiency among older adults living in the community [61] and institutions [47]. A further study of 632 long-term care residents in Canada, who were aged 65 and over, also reported a dietary inadequacy of zinc [62].…”
Section: Zincsupporting
confidence: 91%
“…In the current analysis, 'sometimes' and 'often' receiving eating assistance were amalgamated to provide a sufficiently large group for comparison to those who received no eating assistance. This likely explains the divergence in findings from the main analysis and that from prior research [26]. Further, as noted in prior M3 analysis, persons requiring eating assistance are commonly prescribed MTDs, which are often lower in key nutrients as compared to regular texture diets [16].…”
Section: Discussionmentioning
confidence: 72%
“…According to Simmons et al (2010), offering residents a variety of foods and fluids in between meals may be a more effective way of improving nutritional status [25]. In the Making the Most of Mealtimes (M3) data set, we have demonstrated that about a third of micronutrients analyzed had high proportions (> 50%) of participants consuming levels below the recommendations [26]. However, limited research has explored the association between intake of specific nutrients or diet quality with malnutrition or low CC in LTC residents.…”
Section: Introductionmentioning
confidence: 98%
“…Dishware colour also did not reduce eating challenges. RLWD often receive eating assistance to mitigate eating challenges and increase food consumption [ 11 , 16 ]. Eating assistance facilitates food intake, regardless of dishware colour [ 12 , 17 , 28 , 29 ].…”
Section: Main Textmentioning
confidence: 99%